Comparison between intradermal tuberculin skin testing and interferon gamma ELISA for diagnosis of bovine tuberculosis in Jabalpur region - BASSESSAR, VARUN; SHRIVASTAV, A B; SWAMY, MADHU; ROKDE, AMOL (The Indian Journal of Animal Sciences, 2014)
Interferon gamma ELISA was compared with the conventional tuberculin testing for the antemortem diagnosis of bovine tuberculosis. A single intradermal tuberculin skin test (SID) was carried out as per the standard protocol on animals from which 10 ml blood was collected earlier and Mycobacterium bovis gamma interferon ELISA for cattle was performed. Out of the 100 animals tested, 36 animals (36%) were found positive by tuberculin testing and 24% (22% bovine and 2% avian tuberculin) were found positive for interferon gamma. From 36 tuberculin positive cases only 16 (44.44%) were positive for interferon gamma. Interestingly, from 64 tuberculin negative cases, 8 (12.50%) were determined to be positive for interferon gamma. It can be concluded that SID has a high rate of false-positive as well as false-negative results and the specificity of interferon gamma assay was more than SID.